PENGARUH TERAPI MUSIK TERHADAP PERKEMBANGAN KOMUNIKASI ANAK AUTIS DI KIDDY AUTISM CENTRE KOTA JAMBI TAHUN 2011 - Susi Widiawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Based on data center Kiddy autism therapy Autism Centre in 2008-2010, it is known that the number of children who have autistic children has increased from 43 in 2008 to 51 children in 2009, in 2010 as many as 56 children and from January to July 2011, 47 children . While the results of observations conducted on 12 children with autism aged 3-5 years, it is known that the second child has a communication disorder the child has a mild and 10 moderate communication disorders.The object of the research is the autistic child is in school autism Autism Center Kiddy many as 10 children aged 3-5 years.The study design used is a pre-experimental design with pre-test and post-test one group design. The statistical test used is dependent T test. Sampling in this study by means of purposive samplingFrom the results, the communication development of children with autism before music therapy with a mean of 3.00, median 3.00 standard deviation of 0.00 and minimum and maximum values from 3.00 to 3.00, while the development of children's communication after the music therapy mean 2.70, median 3.00, standard deviation of 0.48 and minimum and maximum values from 2.00 to 3.00. Known of the effect of music therapy on the development of communication in children with autism Autism Center Kiddy City of Edinburgh, with a p-value = 0.001 (p <0.005)Kiddy Autism Center should maximize the application of music therapy on children with autism to overcome communication developmental disorders experienced by children. Then do approach the parents of children with autism in order to implement music therapy at home.Keywords: music therapy, the development of communication.